Patients' intention to consume prescribed and non‐prescribed medicines: A study based on the theory of planned behaviour in selected European countries. (19th August 2017) - Kamekis, A.; Bertsias, A.; Moschandreas, J.; Petelos, E.; Papadakaki, M.; Tsiantou, V.; Saridaki, A.; Symvoulakis, E. K.; Souliotis, K.; Papadakis, N.; Faresjö, T.; Faresjö, A.; et al.
Summary: What is known and objective: Polypharmacy has a significant impact on patients' health with overall expenditure on over‐the‐counter (OTC) medicines representing a substantial burden in terms of cost of treatment. The aim of this study, which was conducted within the framework of a European Project funded by the European Union under the Seventh Framework Programme and was entitled OTC‐SOCIOMED, was to report on possible determinants of patient behaviour regarding the consumption of medicines, and particularly OTCs, in the context of primary care. Methods: A multicentre, cross‐sectional study was designed and implemented in well‐defined primary healthcare settings in Cyprus, the Czech Republic, France, Greece, Malta and Turkey. Patients completed a questionnaire constructed on the basis of the theory of planned behaviour (TPB), which was administered via face‐to‐face interviews. Results and discussion: The percentage of patients who had consumed prescribed medicines over a 6‐month period was consistently high, ranging from 79% in the Czech Republic and 82% in Turkey to 97% in Malta and 100% in Cyprus. Reported non‐prescribed medicine consumption ranged from 33% in Turkey to 92% in the Czech Republic and 97% in Cyprus. TPB behavioural antecedents explained 43% of the variability of patients' intention to consume medicines in Malta and 24% in Greece, but only 3% in Turkey. Subjective norm was a significant predictor of the intention to consume medicines in all three countries (Greece, Malta and Turkey), whereas attitude towards consumption was a significant predictor of the expectation to consume medicines, if needed. What is new and conclusion: This study shows that parameters such as patients' beliefs and influence from family and friends could be determining factors in explaining the high rates of medicine consumption. Factors that affect patients' behavioural intention towards medicine consumption may assist in the formulation of evidence‐based policy proposals and inform initiatives and interventions aimed at increasing the appropriate use of medicines. Abstract : This article provides the parameters which influence patients' consumption for the use of over the counter medicines and also confer evidence‐based policy proposals for the appropriate use of medicines.